PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN HPP UNTUK UMKM ABON IKAN DI DESA SEBONG PEREH - Alamsyahbana, M. Isa; Sulastri, Dini; Jacky, Jacky; Pramita, Maharani Eka; Audina, Yulia Putri; Nurmalasari, Nurmalasari; Wulandari, Wina; Fajriyani, Suzan; Gunawan, Syahrul; Nursyalim, Alwi Dwi; Mareta, Karina Vivinanda (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Micro, Small and Medium Enterprises located in the Bintan Island area mostly do not have or are unable to prepare simple financial reports, even though the role of simple financial records is very important in an MSME business unit, because having financial records certainly makes it easier for businesses to monitor income and expenses in the business and what kind of selling price must be set so that the business makes a profit.The factor that causes difficulty in preparing simple financial reports for Micro, Small and Medium Enterprises is the absence of a clear economic entity. This happens because most MSMEs are unable to differentiate between business activities and personal activities, so company assets are recognized as personal property and vice versa. From this statement, it is difficult to clearly identify the economic entity.This research was conducted at the UMKM "Abon Ikan" on October 28 2023, located in Sebong Pereh Village, Bintan Regency. This type of research is descriptive qualitative with a case study approach. The research results show that in Sebong Pereh Village there are Micro, Small and Medium Enterprises (MSMEs) that are building fish floss businesses, but in carrying out their business activities there is no recording system in any form. So after we teach about preparing simple financial reports and calculating COGS, it really helps Micro, Small and Medium Enterprises (MSMEs) because it can help MSMEs to see the financial condition of their business and obtain the maximum level of profit. Apart from that, this can also help business owners to know the amount of expenses and income that are more neatly arranged and business owners can find out the amount of profit earned every month.